Major depression is not associated with blunting of aversive responses; evidence for enhanced anxious anticipation. - Christian Grillon; Jose A Franco-Chaves; Camilo F Mateus; Dawn F Ionescu; Carlos A Zarate (PLoS ONE)
According to the emotion-context insensitivity (ECI) hypothesis, major depressive disorder (MDD) is associated with a diminished ability to react emotionally to positive stimuli and with blunting of defensive responses to threat. That defensive responses are blunted in MDD seems inconsistent with the conceptualization and diagnostic nosology of MDD. The present study tested the ECI hypothesis in MDD using a threat of shock paradigm. Twenty-eight patients with MDD (35.5±10.4 years) were compared with 28 controls (35.1±7.4 years). Participants were exposed to three conditions: no shock, predictable shock, and unpredictable shock. Startle magnitude was used to assess defensive responses. Inconsistent with the ECI hypothesis, startle potentiation to predictable and unpredictable shock was not reduced in the MDD group. Rather, MDD patients showed elevated startle throughout testing as well as increased contextual anxiety during the placement of the shock electrodes and in the predictable condition. A regression analysis indicated that illness duration and Beck depression inventory scores explained 37% (p<.005) of the variance in patients' startle reactivity. MDD is not associated with emotional blunting but rather enhanced defensive reactivity during anticipation of harm. These results do not support a strong version of the ECI hypothesis. Understanding the nature of stimuli or situations that lead to blunted or enhanced defensive reactivity will provide better insight into dysfunctional emotional experience in MDD.